Pengetahuan Ibu Tentang Manajemen Laktasi Dengan Perilaku Pemberian ASI Ekslusif - Heri Priatna; Evi Nurafiah (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
ABSRACT Background: Lactation management is all the efforts made to help mothers achieve success in breastfeeding their babies. Implementation of breastfeeding can be done properly and correctly if there is complete information about the benefits of breastfeeding and lactation management. Exclusive breastfeeding is inhibited by several things such as breastfeeding behavior that is less supportive about lactation management, awareness of the importance of breastfeeding. Research Objectives: to determine the relationship of maternal knowledge about lactation management with exclusive breastfeeding behavior in the work area of ​​Tangerang Central Tangerang Health Center in 2019. Research Method: this research is a quantitative research with a descriptive correlational design. Data collection is done by questionnaire. The number of respondents was 89 mothers who have babies aged 6-12 months with simple random sampling technique. The data obtained were processed statistically using the chi square formula. Research Results: Based on the analysis results obtained that of 89 respondents of mothers who have babies aged 6-12 months, 73.0% have good knowledge, and 27.0% have less knowledge. As many as 68.5% of good behavior in exclusive breastfeeding and 31.5% of the lack of behavior in exclusive breastfeeding. Conclusion: Based on the results of the study, there is a relationship between the knowledge of mothers about lactation management with exclusive breastfeeding behavior in the working area of ​​the tangerang tangerang health center in 2019 (p value ≤ 0.05) namely p value: 0.011